2022
DOI: 10.1177/08862605211072266
|View full text |Cite
|
Sign up to set email alerts
|

Perpetration of Image-Based Sexual Abuse: Extent, Nature and Correlates in a Multi-Country Sample

Abstract: Image-based sexual abuse (IBSA) is a form of technology-facilitated abuse in which intimate (nude or sexual) images of a person are taken, distributed, or threats are made to distribute the images, without a person’s consent. It is an increasingly criminalized form of sexual abuse, and yet little is known about the perpetrators of these harms, including the extent, relational nature and correlates of perpetration. This article reports on the first multi-country survey study to comprehensively investigate IBSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 59 publications
(130 reference statements)
2
33
1
Order By: Relevance
“…Our data shows gender differences between groups, with males being 2.9 times more likely to engage in IBSA perpetration than females. These results are in line with previous research ( 11 , 15 , 16 , 24 , 26 , 28 ). Other demographic variables showed slight differences between IBSA perpetrators and non-perpetrators.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our data shows gender differences between groups, with males being 2.9 times more likely to engage in IBSA perpetration than females. These results are in line with previous research ( 11 , 15 , 16 , 24 , 26 , 28 ). Other demographic variables showed slight differences between IBSA perpetrators and non-perpetrators.…”
Section: Discussionsupporting
confidence: 94%
“…Overall, our results showed that 20.7% of the original sample reported engaging in at least one IBSA perpetration behavior in the previous year, which is higher than the results obtained in previous research, with rates that range between 5.1 and 35% ( 11 , 15 , 24 28 ). Out of the group of participants who reported engaging in IBSA perpetration behaviors, 63.4% forwarded sexual content they had received, 6% took a sexual picture of a victim and forwarded it without consent, 23.9% pressured someone to receive sexual content and 6.7% threatened someone to receive sexual content.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Weights were developed for the sample that adjust for nonresponse (raking adjustment to the 2021 age-specific benchmarks for gender, educational level, race and ethnicity, household income, US Census region, and metropolitan status) and the prioritization of lower base-rate incidents among those with multiple exposures. The study operationalized several distinct offenses that occur under broader concepts from the literature, 5,8,14 such as image-based sexual abuse, online grooming, and nonconsensual sexting.…”
Section: Methodsmentioning
confidence: 99%